Coping with customer misconduct through communities of practice - Mebarki, Lamine; Suquet, Jean-Baptiste (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
Communities of practice are presented as a stimulating organizational form because they provide an answer to the formal organizational limits. This article mobilises the concept of CoP in the context of coping with customer misconduct in services, recognized today as a major issue in service management. The literature on coping offers insight on employees’ practices for dealing with difficult customers, but it overlooks the critical process of these practices’ development. Through an ethnographic study of a social agency, we suggest a CoP perspective to reveal how frontline employees interact in their community to develop coping practices related to customer misconduct.